Vitamin D for Recovery of COVID-19 in Patients With Chronic Kidney Disease - Chiang, Wen-Fang; Hsiao, Po-Jen; Chan, Jenq-Shyong (Frontiers in Nutrition, 2022)
The severity of coronavirus disease 2019 (COVID-19) is determined not only by the viral damage to cells but also the immune reaction in the host. Except therapeutic interventions targeting viral infection, immunoregulation may be helpful in management of COVID-19. Vitamin D exerts effects on both innate and adaptive immunity, and subsequently modulates immune responses to bacteria and viruses. Patients with chronic kidney disease (CKD) frequently have vitamin D deficiency and increased susceptibility to infection, suggesting the potential role of vitamin D in this vulnerable population. In this paper, we review the alterations of immune systems, the risk of COVID-19 infections and mechanisms of vitamin D action in the pathogenesis of COVID-19 among CKD patients. Previous studies have shown vitamin D deficiency can affect the outcomes of COVID-19. Supplementing vitamin D during the treatment may be protective against COVID-19. Future studies including randomized control trial is warranted to determine the effect of vitamin D supplementation for recovery of COVID-19 in CKD patients.